2007
DOI: 10.1177/021849230701500515
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Rheumatic Mitral Stenosis with Multiple Ventricular Septal Defects

Abstract: Congenital heart disease is related to events occurring in the embryonal stage, while rheumatic heart disease is a sequela of immune-mediated damage following streptococcal infection. We report an unusual association of multiple ventricular septal defects and severe pulmonary arterial hypertension with rheumatic mitral stenosis in a 7-year-old girl. This case highlights the need for careful examination for coexisting rheumatic disease in late presentations of congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Among the previous cases, both the cases had undergone surgical correction of VSD and MVR. 5,6 But, in our case surgical correction was not possible due to irreversibility of PAP & PVRI after O2 administration though PTMC could be done as mitral valve was suitable for it. 8 But due to refusal by parents we couldn't do the procedure in our case and she was managed medically only.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Among the previous cases, both the cases had undergone surgical correction of VSD and MVR. 5,6 But, in our case surgical correction was not possible due to irreversibility of PAP & PVRI after O2 administration though PTMC could be done as mitral valve was suitable for it. 8 But due to refusal by parents we couldn't do the procedure in our case and she was managed medically only.…”
Section: Discussionmentioning
confidence: 68%
“…4 There are few case reported in the literature where RHD with severe MS was associated with VSD. 5,6 Another case reported in 1956, which showed association between RHD and Eisenmenger syndrome. 7 But, our case was very peculiar because she had presented with the clinical features Eisenmenger syndrome as the primary Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 30 When septal defects co-exist with valvular heart disease, there is an increases risk of developing pulmonary hypertension and symptoms of heart failure tend to occur at an earlier age. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with VSD who again develop mitral valve disease are at dual risk of developing severe pulmonary hypertension from both precapillary and post capillary physiologies increasing the risk of adverse outcomes. In sub-Saharra Africa where rheumatic heart disease is common, the association of rheumatic mitral stenosis with atrial septal defect (Lutembacher syndrome) 10 - 14 and that of VSD have also been reported. 14 However, the occurrence of VSD and rheumatic mitral valve disease with isolated regurgitation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation